NUOVE MICROFACIES DEL TRIAS SUPERIORE NELLE BRECCE Dl MONTE GALERO (ALPI MARITTIME) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Late Triassic new microfacies are described from the Maritime Alps. They are contained in lithoclasts from the Brecce of M. Galero Formation. The Foraminifera Glomospirella friedli Kristan Tollmann and Agathammina austroalpina Kristan—Tollmann & Tollmann indicating a Late Triassic age were identified. The sedimentary features document a shallow—water, high energy environment with some redeposited particles. An intrabasinal derivation from Prepiemontese (Case Tuberto, Arnasco— Castelbianco) or Brianzonese units is suggested.
Keywords: Upper Triassic; microfacies; Foraminifera; facies analysis; Maritime Alps.